Neodymium 1d Systems: Targeting New Sources for Field-Induced Slow Magnetization Relaxation - Aravena-Ponce, D; Aravena-Ponce, D (Royal Society of Chemistry, 2015)
Two non-isostructural homometallic 1D neodymium species displaying field-induced slow magnetization relaxations are presented together with theoretical studies. It is established that both systems are better described as organized 1D single molecule magnets (SMMs). Studies show great potential of NdIII ions to provide homometallic chains with slow magnetic relaxation. © The Royal Society of Chemistry.